Dinâmica de estruturas prismáticas laminares - consideração de cargas móveis - Guerreiro, João Nisan Correia (1977)
Dynamic analysis of laminated structures submitted to moving loads. The formulation of the problem makes use of Hamilton's principle and the linear theory of thin plates. Associated with the Fourier series, the finite element method is used to discretize the spatial variables. The resulting system of ordinary differential equations is integrated by means of Newmark's method. Some example problems are analised in order to compare its results with some known solutions.